Electroencephalogram Abnormalities and Epilepsy in Autism Spectrum Disorders: Clinical and Electroencephalogram Findings - Hanci, Fatma; Türay, Sevim; Öztürk, Yusuf; Kabakus, Nimet (Journal of Pediatric Epilepsy, 2021)
It has been known for several decades that epilepsy and autism spectrum disorders (ASD) are related to each other. Epilepsy frequently accompanies ASD. The purpose of this study was to investigate relationship between clinical and electroencephalogram (EEG) findings in ASD patients and to identify EEG characteristics that may create a disposition to epilepsy in ASD by examining differences in clinical and EEG findings between patients diagnosed with ASD without epilepsy and ASD with epilepsy. A total of 102 patients aged 2 to 18 years and diagnosed with ASD based on Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5) diagnostic criteria between January 2017 and June 2019 were included in the study. Patients were assigned into two groups: (1) ASD with epilepsy and (2) ASD without epilepsy. Clinical findings were retrieved from patients' files, and EEG findings from first EEG records in the EEG laboratory at the time of diagnosis. EEG findings were defined as central, parietal, frontal, temporal, or generalized, depending on the location of rhythmic discharges. The incidence of epilepsy in our ASD patients was 33.7% and that of febrile convulsion was 4%. Generalized motor seizures were the most common seizure type. Epileptic discharges most commonly derived from the central and frontal regions. These abnormalities, especially frontal and central rhythmic discharges, may represent a precursor for the development of epilepsy in ASD patients.
Keywords: autism spectrum disorders; electroencephalography; epilepsy